Hollow particles and method for manufacturing same

By using monomer components of divinyl aromatic compounds and monovinyl aromatic compounds to form hollow particles, and through specific manufacturing methods and cleaning steps, the problem that hollow particles in the prior art are difficult to achieve low dielectric constant and low dielectric loss tangent in high-frequency communication systems, and the dielectric characteristics optimization of resin compositions suitable for 5G and later high-frequency communication systems is achieved.

CN119816528APending Publication Date: 2025-04-11SANSUI CO LTD OOMIYA SAITAMA JP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380063519.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-25
Filing Date
2023-11-22
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When used in the fifth generation (5G) and later high-frequency communication systems, it is difficult to achieve sufficient low dielectric constant and low dielectric loss tangent.

Method used

The hollow particles formed by using a polymer containing a monomer component of a divinyl aromatic compound and a monovinyl aromatic compound, and the production method in which the dielectric loss tangent is 1.00×10-3 or less is measured by a cavity resonator method. The method includes mixing the monomer component with a hydrophobic solvent to form an oil-based mixed liquid, then mixing it with water to form an emulsion, and polymerizing the monomer component in the emulsion to form a polymer containing a hydrophobic solvent. Finally, the hydrophobic solvent contained in the polymer is removed by cleaning.

Benefits of technology

The resin composition is low dielectric constant and low dielectric loss tangent, and is suitable for electronic equipment in high-frequency communication systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005295428180000131
    Figure BDA0005295428180000131
Patent Text Reader

Abstract

Provided are: hollow particles which are capable of achieving a low dielectric constant and a low dielectric loss tangent in a resin composition; and a method for producing the hollow particles. The hollow particles according to the present invention have a shell part formed from a polymer containing monomer components of a divinyl aromatic compound and a monovinyl aromatic compound, and a hollow part surrounded by the shell part, and have a dielectric loss tangent of 1.00 * 10-3 or less as measured by a cavity resonator method (frequency 10 GHz (room temperature)). The hollow particles can be produced by mixing the monomer component with a predetermined hydrophobic solvent, further mixing with water to obtain an emulsion, polymerizing the monomer component in the emulsion, and washing the obtained polymer with water and an organic solvent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to hollow particles and a method for producing the same. More specifically, the present invention relates to hollow particles and a method for producing the same that can achieve low dielectric constant and low dielectric loss tangent of a resin composition that is a material for electronic circuit substrates, laminated substrates, sealing materials, bottom filling materials, chip bonding materials, prepregs, etc. used in electronic devices corresponding to fifth-generation (5G) and later high-frequency communication systems. Background Art

[0002] Resin compositions containing thermosetting resins such as epoxy resins, polyimide resins, maleimide resins, and phenolic resins, and thermoplastic resins such as polyethylene resins, acrylic resins, polycarbonate resins, polyarylate resins, and fluororesins are widely used as materials for electronic circuit boards, build-up substrates, sealing materials, underfill materials, chip bonding materials, prepregs, etc. for electronic devices, etc. In particular, various resin compositions have been developed in recent years to meet the requirements of high-frequency communication systems such as 5G and beyond, which require more excellent low dielectric properties.

[0003] Patent document 1 describes a resin composition comprising a thermosetting resin and hollow particles, wherein the shell of the hollow particles has a single-layer structure formed by any of a polymer and a copolymer of a cross-linking monomer, and a copolymer of the cross-linking monomer and a monofunctional monomer, the average particle size of the hollow particles is 0.1 to 30 μm, the shell thickness of the hollow particles is 0.01 to 4 μm, and the volume ratio of the internal voids of the hollow particles to the total volume is 40 to 80%.

[0004] Patent Document 2 describes a hollow polymer particle characterized in that it is composed of a shell and a hollow part, and the shell has a single-layer structure formed by a polymer or copolymer of at least one cross-linking monomer, or a copolymer of at least one cross-linking monomer and at least one monofunctional monomer.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2004 / 67638

[0008] Patent Document 2: Japanese Patent Application Publication No. 2002-80503 Summary of the invention

[0009] Problem that the invention aims to solve

[0010] However, for the hollow particles described in Patent Documents 1 to 2, if they are used in electronic devices corresponding to fifth-generation (5G) and later high-frequency communication systems, it cannot be said that they can achieve sufficiently low dielectric constants and low dielectric loss tangents (especially low dielectric loss tangents).

[0011] Therefore, an object of the present invention is to provide hollow particles and a method for producing the same which can achieve a low dielectric constant and a low dielectric loss tangent of a resin composition.

[0012] Solutions for solving problems

[0013] The present invention provides a method for producing hollow particles, wherein the hollow particles have a shell portion formed of a polymer containing monomer components of a divinyl aromatic compound and a monovinyl aromatic compound and a hollow portion surrounded by the shell portion, and the dielectric loss tangent measured by a cavity resonator method (frequency 10 GHz (room temperature)) is 1.00×10 -3 Hereinafter, the method has the following steps:

[0014] Step (a), mixing the aforementioned monomer components and a normal alkane solvent, an isoalkane solvent or a cycloalkane solvent having 9 or more carbon atoms as a hydrophobic solvent to obtain an oil-based mixed liquid;

[0015] Step (b), mixing the oil-based mixed liquid and water to obtain an emulsion in which the oil-based mixed liquid is dispersed in the water;

[0016] Step (c), polymerizing the monomer components in the emulsion to form the polymer containing the hydrophobic solvent; and

[0017] Step (d): step (d1) washing the polymer with water, and step (d2) washing the polymer with an organic solvent, thereby removing the hydrophobic solvent contained in the polymer.

[0018] The present invention provides hollow particles having a shell portion formed of a polymer containing monomer components of a divinyl aromatic compound and a monovinyl aromatic compound and a hollow portion surrounded by the shell portion.

[0019] The dielectric loss tangent of the hollow particles measured by the cavity resonator method (frequency 10 GHz (room temperature)) was 1.00×10 -3 the following.

[0020] Effects of the Invention

[0021] According to the present invention, hollow particles capable of achieving a low dielectric constant and a low dielectric loss tangent of a resin composition and a method for producing the same can be provided. DETAILED DESCRIPTION

[0022] Hollow particle of the present invention has: the shell formed by the polymer of the monomer component comprising divinyl aromatic compound and the hollow part surrounded by the aforementioned shell.It should be noted that, as described later, there is air in the hollow part of hollow particle, and the hydrophobic solvent (and then unreacted monomer, polymerization initiator, dispersion stabilizer etc.) used during manufacture is almost not residual.Such hollow particle has low dielectric constant and low dielectric loss tangent, therefore can realize the low dielectric constant and low dielectric loss tangent of the resin composition compounded with the hollow particle.

[0023] The divinyl aromatic compound contained in the monomer component used to synthesize the polymer forming the shell has two double bonds with low polarity, so the polymer obtained by polymerizing the divinyl aromatic compound becomes a high molecular cross-linked body with low polarity, which can achieve low dielectric constant and low dielectric loss tangent of the hollow particles formed therefrom. As divinyl aromatic compounds, divinylbenzene (including isomers such as o-divinylbenzene, m-divinylbenzene, and p-divinylbenzene), divinylbiphenyl (including isomers such as 4,4'-divinylbiphenyl and 3,3'-divinylbiphenyl), and divinylnaphthalene (including isomers such as 1,5-divinylnaphthalene and 1,3-divinylnaphthalene), and compounds in which at least one of the hydrogen atoms of their aromatic rings is substituted by a substituent, etc. As substituents, alkyl groups, alkoxy groups, and alkylthio groups having 1 to 10 carbon atoms; aryl groups, aryloxy groups, and arylthio groups having 6 to 10 carbon atoms; cycloalkyl groups having 3 to 10 carbon atoms; halogen atoms; hydroxyl groups; and mercapto groups, etc. Among them, divinylbenzene (including isomers such as o-divinylbenzene, m-divinylbenzene and p-divinylbenzene) is preferred. The divinyl aromatic compound may be used alone or in combination of two or more.

[0024] The monomer component for synthesizing the polymer forming the shell portion can be only the above-mentioned divinyl aromatic compound, but preferably includes a monomer that can copolymerize with the divinyl aromatic compound. The polymer obtained by polymerizing the divinyl aromatic compound becomes a high molecular crosslinked body with low polarity, so the monomer that can copolymerize with the divinyl aromatic compound is preferably a monomer with a double bond with low polarity. As a monomer that can copolymerize with the divinyl aromatic compound, monovinyl aromatic compounds, monoolefin compounds, diolefin compounds, etc. can be listed. Among them, monovinyl aromatic compounds are preferably used. The copolymerizability of monovinyl aromatic compounds and divinyl aromatic compounds is good, and there is a double bond with low polarity, so the polymer obtained by copolymerizing with the divinyl aromatic compound becomes a high molecular crosslinked body with lower polarity, and the further low dielectric constant and low dielectric loss tangent of the hollow particles formed therefrom can be realized. The monomer that can copolymerize with the divinyl aromatic compound can be used alone, or two or more can be used in combination.

[0025] As monovinyl aromatic compounds, styrene compounds such as styrene, α-methylstyrene, β-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, α-ethylstyrene, β-ethylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, α-cyclopropylstyrene, β-cyclopropylstyrene and 4-tert-butylstyrene; vinylnaphthalene compounds such as 1-vinylnaphthalene and 2-vinylnaphthalene; vinylbiphenyl compounds such as 4-vinylbiphenyl and 3-vinylbiphenyl, etc. can be listed. Among them, styrene compounds are preferred, and styrene is more preferred. Monovinyl aromatic compounds can be used alone or in combination of two or more.

[0026] The amount of the monomer copolymerizable with the divinyl aromatic compound can be appropriately adjusted according to the purpose. From the viewpoint of exerting the characteristics of the copolymerized divinyl aromatic compound, it is preferably set to 90 parts by weight or less, more preferably 70 parts by weight or less, and further preferably 60 parts by weight or less in 100 parts by weight of the monomer component. It is also possible not to use the monomer copolymerizable with the divinyl aromatic compound. From the viewpoint of achieving further low dielectric constant and low dielectric loss tangent by copolymerization, it is preferably set to 10 parts by weight or more, more preferably 30 parts by weight or more, and further preferably 40 parts by weight or more in 100 parts by weight of the monomer component.

[0027] In the present invention, for example, by preparing an emulsion in which the above-mentioned monomer components are dispersed in water as an oil phase and suspending and polymerizing the monomer components, hollow particles composed of polymers of the monomer components can be formed. Specifically, first, the above-mentioned monomer components are mixed with a hydrophobic solvent to obtain an oil-based mixed liquid (process (a)). Next, the above-mentioned oil-based mixed liquid is mixed with water to obtain an emulsion in which the above-mentioned oil-based mixed liquid is dispersed in the above-mentioned water (process (b)). Then, the above-mentioned monomer components are polymerized in the above-mentioned emulsion (process (c)). Thus, a shell portion composed of the above-mentioned polymer and containing the above-mentioned hydrophobic solvent can be formed.

[0028] The hydrophobic solvent for preparing the oil-based mixed solution comprising the monomer component is preferably capable of dissolving the monomer component and having low compatibility with the polymer (or copolymer) of the monomer component. As the hydrophobic solvent, aliphatic hydrocarbon solvents such as normal alkane solvents (including normal alkanes with a carbon number less than 20), isoalkane solvents and cycloalkane solvents are preferably used. Among them, the normal alkane solvents, isoalkane solvents or cycloalkane solvents with a carbon number of more than 9 are more preferably used. A hydrophobic solvent can be used alone, or two or more are used in combination.

[0029] It should be noted that, as the normal alkane with a carbon number less than 20, n-pentane, n-hexane, n-heptane, n-octane, n-nonane, n-decane, n-undecane, n-dodecane, n-tridecane, n-tetradecane, n-pentadecane, n-hexadecane, n-heptadecane, n-octadecane and n-nonadecane etc. can be listed. The carbon number of the normal alkane is preferably more than 9. As the normal alkane solvent, NORPAR 10, NORPAR 12, NORPAR 13 and NORPAR 15 (all are trade names of Exxon Mobil Corporation) etc. can be listed. As the isomeric alkane solvent, Isoper C, Isoper E, Isoper G, Isoper H, Isoper L, Isoper M and Isoper V (all are trade names of Exxon Mobil Corporation) etc. can be listed. Examples of the cycloalkane solvent include Exxol Hexane, Exxol Heptane, Exxol DSP80 / 100, Exxol D30, Exxol D40, Exxol D60, Exxol D80, Exxol D95, Exxol D110, and Exxol D130 (all trade names manufactured by Exxon Mobil Corporation).

[0030] The mixing ratio of the monomer component and the hydrophobic solvent can be appropriately adjusted according to the purpose. From the viewpoint of sufficiently polymerizing the monomer component, the monomer component is preferably 10 to 900 parts by weight, more preferably 30 to 700 parts by weight, relative to 100 parts by weight of the hydrophobic solvent.

[0031] It is preferred to mix a polymerization initiator for polymerizing the monomer components in the oil-based mixed liquid. The polymerization initiator can initiate the polymerization of the divinyl aromatic compound (and the monomer copolymerizable therewith), and is preferably a polymerization initiator soluble in a hydrophobic solvent. As the polymerization initiator, a thermal free radical polymerization initiator that breaks by heat to generate free radicals and a photo-free radical polymerization initiator that breaks by light to generate free radicals can be listed. Considering the suspension polymerization of the monomer components, a thermal free radical polymerization initiator is preferably used. As a thermal free radical polymerization initiator, organic peroxides such as benzoyl peroxide, lauroyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, diisopropyl hydroperoxide, dicumyl peroxide, di-tert-butyl peroxide and tert-butyl peroxybenzoate can be listed; azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile and 2,2'-azobis-2,4-dimethylvaleronitrile, etc. Among them, it is preferably an organic peroxide, and more preferably benzoyl peroxide. The polymerization initiator may be used alone or in combination of two or more.

[0032] The amount of the polymerization initiator can be appropriately adjusted depending on the purpose, and is preferably 0.1 to 5.0 parts by weight, more preferably 0.3 to 3.0 parts by weight, based on 100 parts by weight of the monomer component, from the viewpoint of sufficiently polymerizing the monomer component.

[0033] As water for preparing emulsion by mixing with oil-based mixed liquid, ion exchange water is preferred. In addition, in the oil-based mixed liquid, an aqueous mixed liquid formed by mixing a dispersion stabilizer for stably dispersing the droplets of the oil-based mixed liquid in water can also be mixed in the water. As the dispersion stabilizer, nonionic surfactants, anionic surfactants, cationic surfactants, zwitterionic surfactants and polymeric surfactants can be listed, preferably polymeric surfactants. As the polymeric surfactant, polyvinyl alcohol-based surfactants (polyvinyl alcohol or its modified body), casein-based surfactants, carboxymethyl cellulose-based surfactants and acrylic surfactants can be listed. Dispersion stabilizers can be used alone or in combination of two or more.

[0034] The amount of the dispersion stabilizer added can be appropriately adjusted depending on the purpose. From the viewpoint of stably dispersing droplets of the oil-based mixed liquid in water, it is preferably 1 to 30 parts by weight, more preferably 3 to 20 parts by weight, and even more preferably 4 to 15 parts by weight relative to 100 parts by weight of the oil-based mixed liquid.

[0035] The oil-based mixed liquid and water (or water-based mixed liquid) can be mixed using, for example, a homogenizer emulsifier. The rotation speed and rotation time of the homogenizer emulsifier can be appropriately adjusted to form a state in which droplets of the oil-based mixed liquid of a desired size are dispersed in water. By suspending and polymerizing the monomer components in the emulsion thus obtained, the polymer formed in the droplets of the oil-based mixed liquid moves or precipitates near the surface of the droplets (near the interface between water and the oil-based mixed liquid), and hollow particles having a shell portion composed of the polymer can be formed. The temperature and time of the suspension polymerization can be appropriately adjusted to form the desired shell portion.

[0036] However, the shell portion consisting of the obtained polymer contains a hydrophobic solvent. And then, it is also possible to have unreacted monomers, polymerization initiators, dispersion stabilizers, etc. If they remain, the dielectric properties of the hollow particles obtained, particularly the dielectric loss tangent, tend to significantly increase. For example, in patent documents 1 and 2, it is recorded that the hollow particles obtained by suspension polymerization are filtered and heated and dried, but the hydrophobic solvent, etc., cannot be fully removed in this way, and the dielectric properties of the hollow particles obtained, particularly the dielectric loss tangent, significantly increase.

[0037] Therefore, in the present invention, the hydrophobic solvent contained in the polymer is removed by washing the obtained polymer (step (d)). Thus, the hydrophobic solvent contained in the polymer (and further the unreacted monomers, polymerization initiator, dispersion stabilizer, etc.) can be fully removed, and the dielectric constant and dielectric loss tangent of the obtained hollow particles can be reduced.

[0038] It is particularly preferred to wash the aforementioned polymer with water (step (d1)) and to wash the aforementioned polymer with an organic solvent (step (d2)). Step (d1) and step (d2) are preferably performed multiple times (about 2 to 4 times), respectively. As an organic solvent, any solvent that is compatible with the hydrophobic solvent (and further unreacted monomers, polymerization initiators, dispersion stabilizers, etc.) may be used, and examples thereof include aliphatic hydrocarbons such as hexane, heptane, octane, and cyclohexane; aromatic hydrocarbons such as benzene and toluene; nitrated hydrocarbons such as nitromethane and nitroethane; halogenated hydrocarbons such as dichloromethane, chloroform, dibromomethane, bromoform, diiodomethane, and iodoform; alcohols such as methanol, ethanol, and isopropanol; ethers such as diethyl ether and tetrahydrofuran; esters such as ethyl acetate; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; and polar solvents such as dimethylformamide and dimethyl sulfoxide, etc. Among them, alcohols and / or ketones are preferred. The organic solvent may be used alone or in combination of two or more. When the step (d2) is performed a plurality of times, the same organic solvent may be used or different organic solvents may be used.

[0039] The washed hollow particles may be dried by appropriately heating or reducing the pressure.

[0040] Thus, it is possible to obtain a highly purified hollow particle with a shell portion formed by a polymer of a monomer component comprising a divinyl aromatic compound and a hollow portion surrounded by the aforementioned shell portion. It should be noted that there is air in the hollow portion of a hollow particle, and the hydrophobic solvent (and then unreacted monomer, polymerization initiator, dispersion stabilizer, etc.) used during manufacture is almost non-residual, and therefore, the hollow particle has low dielectric constant and low dielectric loss tangent, and it is possible to achieve low dielectric constant and low dielectric loss tangent of the resin composition compounded with the hollow particle.

[0041] The average particle size (median particle size) of the hollow particles is preferably 0.05 to 50 μm, more preferably 0.1 to 30 μm. The average particle size (median particle size) of the hollow particles can be measured, for example, using a laser diffraction / scattering particle size distribution measuring apparatus.

[0042] The average hollowness of the hollow particles is preferably 10 to 90%, more preferably 20 to 80%. It should be noted that the hollowness of the hollow particles can be measured using a scanning electron microscope or a transmission electron microscope to measure the inner diameter and outer diameter of the hollow particles, and calculated using the following calculation formula. For example, the average hollowness can be calculated from the hollowness of more than 10 randomly selected hollow particles.

[0043] Hollowness (%) = (inner diameter of hollow particle / outer diameter of hollow particle) 3 ×100

[0044] In addition, the hollowness ratio of the hollow particles can also be calculated by comparing the sedimentation properties with particles (dense particles) formed of the same material and having no hollow portion.

[0045] The dielectric loss tangent of the hollow particles measured by the cavity resonator method (frequency 10 GHz (room temperature)) is usually less than the dielectric loss tangent of silica (manufactured by Denka Company Limited., trade name: spherical silica FB-950) measured under the same conditions immediately before or immediately after, and more specifically, preferably 2.00×10 -3 Below, more preferably 1.80×10 -3 Below, more preferably 1.50×10 -3 Below, particularly preferably 1.00×10 -3 The dielectric constant of the hollow particles measured by a cavity resonator method (frequency 10 GHz (room temperature)) is usually less than the dielectric constant of silica (manufactured by Denka Company Limited., trade name: spherical silica FB-950) measured under the same conditions immediately before or immediately after, and more specifically, is preferably 3.30 or less.

[0046] The hollow particles of the present invention have low dielectric constant and low dielectric loss tangent, therefore, by being mixed in the electronic circuit substrate, laminated substrate, sealing material, bottom filling material, chip bonding material, prepreg and other materials used in the electronic equipment corresponding to the fifth generation (5G) and subsequent high-frequency communication systems, it is possible to achieve the low dielectric constant and low dielectric loss tangent of the obtained resin composition. As a specific example of resin composition, thermosetting resins such as epoxy resins, polyimide resins, maleimide resins, and phenolic resins can be listed; Thermoplastic resins such as polyethylene resins and fluororesins, etc.

[0047] The resin composition can be obtained by mixing the aforementioned hollow particles with a resin component. The blending ratio can be appropriately adjusted in a manner having desired dielectric properties, and is preferably blended in a manner in which the content of the hollow particles is 1 to 50% by weight. When the resin component is a thermosetting resin, it is preferably cured at room temperature or by heating after mixing.

[0048] The resin composition has a low dielectric constant and a low dielectric loss tangent, and is therefore suitable as a material for electronic circuit substrates, laminated substrates, sealing materials, bottom filling materials, chip bonding materials, prepregs, etc. used in electronic devices corresponding to fifth-generation (5G) and later high-frequency communication systems.

[0049] Example

[0050] <Example 1>

[0051] A reaction apparatus equipped with a stirrer, a 2-liter reaction container, a cooling tube (condenser), a stirring blade, a thermometer, and an oil bath was prepared. An oil-based mixed liquid was prepared by mixing 90 g of divinylbenzene (DVB, isomer mixture), 1.9 g of benzoyl peroxide (BPO, containing 25% by weight of water), and 90 g of Isopar M (a trade name manufactured by Exxon Mobil Corporation, an isoparaffin-based hydrocarbon compound). In addition, an aqueous mixed liquid was prepared by mixing 440 g of deionized water (H2O) and 180 g of a 10% by weight aqueous solution of Kuraray Poval KL-506 (a trade name manufactured by KURARAY CO., LTD., a modified polyvinyl alcohol, degree of polymerization: about 600, degree of saponification: 74 to 80 mol%).

[0052] The above-mentioned aqueous mixed liquid was put into a 2-liter reaction container, and then the above-mentioned oil mixed liquid was added while emulsifying for 2 minutes at a rotation speed of 12000 rpm using a homogenizer emulsifier to obtain a milky white liquid. The obtained milky white liquid was placed in the above-mentioned reaction device, and the liquid temperature was heated to 80° C. with an oil bath while stirring, and a polymerization reaction of divinylbenzene was carried out for about 4 hours, and then further heated to 93° C. and a polymerization reaction of divinylbenzene was carried out for about 4 hours. As a result, an aqueous dispersion of hollow particles 1 was obtained in which a shell composed of a polymer formed by polymerization of divinylbenzene was formed, and a hydrophobic solvent (Isopar M (trade name)) and a dispersion stabilizer (Kuraray Poval KL-506 (trade name)), a polymerization initiator (benzoyl peroxide), residual monomers (divinylbenzene), etc. were present inside.

[0053] The aqueous dispersion was centrifuged at a rotation speed of 19000 rpm and a centrifugal acceleration of 43000 g using a high-speed centrifuge (manufactured by Hitachi High-Technologies Corporation., trade name: himac CR21G), and phase-separated into hollow particles and a transparent aqueous phase, and the transparent aqueous phase was removed. After newly adding deionized water to disperse the hollow particles, the phases were separated using a high-speed centrifuge under the same conditions as above, and the transparent aqueous phase was removed. Hereinafter, the same washing process was performed once (a total of 2 times) with deionized water, the same washing process was performed twice with isopropanol, the same washing process was performed once with methyl ethyl ketone, and the same washing process was performed once with acetone, thereby removing the hydrophobic solvent, dispersion stabilizer, polymerization initiator, residual monomer, etc. present inside the hollow particles 1. Next, the obtained solid component was dried at 80°C for about 24 hours, thereby obtaining a white powder of the hollow particles 1.

[0054] The average particle size (median particle size at a frequency of 50%) of the hollow particles 1 measured using a laser diffraction / scattering particle size distribution measuring device (manufactured by Kuba Seisakusho Co., Ltd., trade name: LA-960) was 4.1 μm. In addition, the hollow ratio (%) of 10 randomly selected hollow particles 1 was calculated based on the inner diameter and outer diameter of the hollow particles 1 measured using a scanning electron microscope [= (inner diameter of hollow particle 1 / outer diameter of hollow particle 1) 3 × 100], and the average value was taken, which was about 50%. Table 1 shows the results of the dielectric constant and dielectric loss tangent of the hollow particles 1 measured by the cavity resonator method (frequency: 10 GHz, room temperature).

[0055] <Example 2>

[0056] Using divinylbenzene (DVB, isomer mixture) 67.5g and styrene (ST) 67.5g instead of divinylbenzene (DVB, isomer mixture) 90g, the mixing amount of benzoyl peroxide (BPO, containing 25% by weight of water) is set to 1.5g, the mixing amount of Isopar M (trade name) is set to 135g, the mixing amount of deionized water is set to 330g, and the mixing amount of 10% by weight Kuraray Poval KL-506 (trade name) aqueous solution is set to 190g. In addition, the white powder of hollow particles 2 is obtained by the same method as Example 1. The average particle size of the hollow particles 2 obtained is 2.9μm, and the average hollow ratio is about 50%. In addition, the results of the dielectric constant and dielectric loss tangent of the hollow particles 2 obtained by measuring are shown in Table 1.

[0057] <Example 3>

[0058] A white powder of hollow particles 3 was obtained by the same method as in Example 2 except that Exxsol D40 (a trade name manufactured by Exxon Mobil Corporation, a cycloparaffinic hydrocarbon compound) was used instead of Isopar M (a trade name). The average particle size of the obtained hollow particles 3 was 2.9 μm, and the average hollow ratio was about 50%. In addition, the results of measuring the dielectric constant and dielectric loss tangent of the obtained hollow particles 3 are shown in Table 1.

[0059] <Example 4>

[0060] Use n-hexadecane (nC 16 H 34 , normal alkane hydrocarbon compound) instead of Isopar M (trade name), a white powder of hollow particles 4 was obtained by the same method as in Example 2. The average particle size of the obtained hollow particles 4 was 3.2 μm, and the average hollow ratio was about 50%. In addition, the results of measuring the dielectric constant and dielectric loss tangent of the obtained hollow particles 4 are shown in Table 1.

[0061] <Example 5>

[0062] Use n-heptane (n-C7H 16 , normal alkane hydrocarbon compound) instead of Isopar M (trade name), a white powder of hollow particles 5 was obtained by the same method as in Example 2. The average particle size of the obtained hollow particles 5 was 5.4 μm, and the average hollow ratio was about 50%. In addition, the results of measuring the dielectric constant and dielectric loss tangent of the obtained hollow particles 5 are shown in Table 1.

[0063] <Example 6>

[0064] Except that the washing process with an organic solvent (isopropyl alcohol, methyl ethyl ketone, acetone) was not performed, a white powder of hollow particles 6 was obtained by the same method as in Example 2. The average particle size of the obtained hollow particles 6 was 2.9 μm, and the average hollow ratio was about 50%. In addition, the results of measuring the dielectric constant and dielectric loss tangent of the obtained hollow particles 6 are shown in Table 1.

[0065] <Example 7>

[0066] Except that the step of washing with deionized water was not performed, a white powder of hollow particles 7 was obtained by the same method as in Example 2. The average particle size of the obtained hollow particles 7 was 2.9 μm, and the average hollow ratio was about 50%. In addition, the results of measuring the dielectric constant and dielectric loss tangent of the obtained hollow particles 7 are shown in Table 1.

[0067] <Comparative Example 1>

[0068] The white powder of hollow particles C2 was obtained by the same method as in Example 2 except that the washing step was not performed. The average particle size of the obtained hollow particles C2 was 2.9 μm, and the average hollow ratio was about 50%. In addition, the results of measuring the dielectric constant and dielectric loss tangent of the obtained hollow particles C2 are shown in Table 1.

[0069] <Comparative Example 2>

[0070] The white powder of hollow particles C3 was obtained by the same method as in Example 3 except that the washing step was not performed. The average particle size of the obtained hollow particles C3 was 2.9 μm, and the average hollow ratio was about 50%. In addition, the results of measuring the dielectric constant and dielectric loss tangent of the obtained hollow particles C3 are shown in Table 1.

[0071] <Comparative Example 3>

[0072] Except that the washing step was not performed, a white powder of hollow particles C4 was obtained by the same method as in Example 4. The average particle size of the obtained hollow particles C4 was 3.2 μm, and the average hollow ratio was about 50%. In addition, the results of measuring the dielectric constant and dielectric loss tangent of the obtained hollow particles C4 are shown in Table 1.

[0073] <Comparative Example 4>

[0074] Table 1 shows the results of measuring the dielectric constant and dielectric loss tangent of commercially available silica (average particle size: 33.8 μm, manufactured by Denka Company Limited, trade name: spherical silica FB-950).

[0075] [Table 1]

[0076]

[0077] The dielectric constants and dielectric loss tangents of hollow particles 1 to 7 obtained in Examples 1 to 7 were lower than those of Comparative Example 4. In particular, in hollow particles C2 to C4 obtained in Comparative Examples 1 to 3 without a washing step, although the dielectric constants were lower than those of Comparative Example 4, the dielectric loss tangents were higher. However, in hollow particles 2 to 4 obtained in Examples 2 to 4 under the same conditions of a washing step using water and a washing step using an organic solvent, the dielectric constants were further reduced and the dielectric loss tangents were significantly reduced compared to the corresponding hollow particles C2 to C4.

[0078] It should be noted that, in the hollow particles 6 obtained in Example 6 (only the cleaning process using water is implemented) and the hollow particles 7 obtained in Example 7 (only the cleaning process using an organic solvent is implemented), the dielectric constant and the dielectric loss tangent are also reduced compared with the hollow particles C2 obtained in Comparative Example 1 (no cleaning process) and Comparative Example 4 (dense particles), but in the hollow particles 2 obtained in Example 2 (both the cleaning process using water and the cleaning process using an organic solvent are implemented), the dielectric constant and the dielectric loss tangent (especially the dielectric loss tangent) are further significantly reduced compared with the hollow particles 6 and 7.

[0079] This specification discloses at least the following inventions.

[0080] [1] A method for producing hollow particles, the hollow particles having a shell portion formed of a polymer containing a monomer component of a divinyl aromatic compound and a hollow portion surrounded by the shell portion, the method comprising the following steps:

[0081] Step (a), mixing the aforementioned monomer components and a hydrophobic solvent to obtain an oil-based mixed liquid;

[0082] Step (b), mixing the oil-based mixed liquid and water to obtain an emulsion in which the oil-based mixed liquid is dispersed in the water;

[0083] Step (c), polymerizing the monomer components in the emulsion to form the polymer containing the hydrophobic solvent; and

[0084] Step (d) is to wash the polymer to remove the hydrophobic solvent contained in the polymer.

[0085] [2] The method for producing hollow particles according to [1], wherein the hydrophobic solvent is a normal alkane solvent, an isoalkane solvent, or a cycloalkane solvent.

[0086] [3] The method for producing hollow particles according to [1] or [2], wherein the divinyl aromatic compound is divinylbenzene.

[0087] [4] The method for producing hollow particles according to any one of [1] to [3], wherein the monomer component further contains a monovinyl aromatic compound.

[0088] [5] The method for producing hollow particles according to [4], wherein the monovinyl aromatic compound is styrene.

[0089] [6] The method for producing hollow particles according to any one of [1] to [5], wherein the step (d) comprises: a step (d1) of washing the polymer with water; and a step (d2) of washing the polymer with an organic solvent.

[0090] [7] The method for producing hollow particles according to [6], wherein the organic solvent is an alcohol and / or a ketone.

[0091] [8] A hollow particle comprising a shell portion formed of a polymer containing a monomer component of a divinyl aromatic compound and a hollow portion surrounded by the shell portion,

[0092] The dielectric loss tangent of the hollow particles measured by the cavity resonator method (frequency 10 GHz (room temperature)) was 2.00×10 -3 the following.

[0093] [9] The hollow particles according to [8], wherein the dielectric constant measured by a cavity resonator method (frequency 10 GHz (room temperature)) is 3.30 or less.

[0094]

[10] The hollow particles according to [7] or [8], wherein the divinyl aromatic compound is divinylbenzene.

[0095]

[11] The hollow particles according to any one of [7] to [9], wherein the monovinyl aromatic compound is styrene.

Claims

1. A method for producing hollow particles, wherein the hollow particles have a shell portion formed of a polymer containing monomer components of a divinyl aromatic compound and a monovinyl aromatic compound and a hollow portion surrounded by the shell portion, and the dielectric loss tangent measured by a cavity resonator method (frequency 10 GHz (room temperature)) is 1.00×10 -3 Hereinafter, the method has the following steps: Step (a), mixing the monomer component and a normal alkane solvent, an isoalkane solvent or a cycloalkane solvent having 9 or more carbon atoms as a hydrophobic solvent to obtain an oil-based mixed liquid; Step (b), mixing the oil-based mixed liquid and water to obtain an emulsion in which the oil-based mixed liquid is dispersed in the water; Step (c), polymerizing the monomer component in the emulsion to form the polymer encapsulating the hydrophobic solvent; and In step (d), the polymer is washed with water in step (d1), and the polymer is washed with an organic solvent in step (d2), thereby removing the hydrophobic solvent contained in the polymer.

2. The method for producing hollow particles according to claim 1, wherein: The divinyl aromatic compound is divinylbenzene.

3. The method for producing hollow particles according to claim 1, wherein: The monovinyl aromatic compound is styrene.

4. The method for producing hollow particles according to claim 1, wherein: In the step (d), the step (d1) and the step (d2) are each performed a plurality of times.

5. The method for producing hollow particles according to claim 1, wherein: The organic solvent is alcohol and / or ketone.

6. The method for producing hollow particles according to claim 1, wherein: The hollow particles have a dielectric constant of 3.30 or less as measured by a cavity resonator method (frequency 10 GHz (room temperature)).

7. A hollow particle comprising a shell portion formed of a polymer containing monomer components of a divinyl aromatic compound and a monovinyl aromatic compound and a hollow portion surrounded by the shell portion, The dielectric loss tangent of the hollow particles measured by the cavity resonator method (frequency 10 GHz (room temperature)) was 1.00×10 -3 the following.

8. The hollow particles according to claim 7, wherein The dielectric constant measured by a cavity resonator method (frequency 10 GHz (room temperature)) was 3.30 or less.

9. The hollow particles according to claim 7, wherein The divinyl aromatic compound is divinylbenzene.

10. The hollow particles according to claim 7, wherein The monovinyl aromatic compound is styrene.

Citation Information

Patent Citations

  • Hollow polymer fine particle and method for producing the same

    JP2002080503A

  • Resin composition containing hollow particles, prepreg containing such composition and laminated sheet

    WO2004067638A1